2022
DOI: 10.1227/ons.0000000000000173
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Network Approach to Competency-Based Training Using a Virtual Reality Neurosurgical Simulation

Abstract: BACKGROUND: The methodology of assessment and training of surgical skills is evolving to deal with the emergence of competency-based training. Artificial neural networks (ANNs), a branch of artificial intelligence, can use newly generated metrics not only for assessment performance but also to quantitate individual metric importance and provide new insights into surgical expertise. OBJECTIVE: To outline the educational utility of using an ANN in the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…The ACDF simulated scenario utilized in this study has been extensively employed by our group to assess surgical expertise. The simulation includes 3 animated steps (neck incision, placement of retractors, and fusion) and 4 deconstructed interactive steps (C4-C5 vertebral disc annulus incision, discectomy, osteophyte removal, and posterior longitudinal ligament removal) [5,6,18]. Each of the interactive simulated steps have been shown to have face, content and construct validity [5].…”
Section: The Virtual Reality Simulator and The Simulated Scenariomentioning
confidence: 99%
See 4 more Smart Citations
“…The ACDF simulated scenario utilized in this study has been extensively employed by our group to assess surgical expertise. The simulation includes 3 animated steps (neck incision, placement of retractors, and fusion) and 4 deconstructed interactive steps (C4-C5 vertebral disc annulus incision, discectomy, osteophyte removal, and posterior longitudinal ligament removal) [5,6,18]. Each of the interactive simulated steps have been shown to have face, content and construct validity [5].…”
Section: The Virtual Reality Simulator and The Simulated Scenariomentioning
confidence: 99%
“…The current study focuses on the first interactive step which consists of performing a 2cm transverse box incision exposing the disc annulus using a virtual No.15 scalpel. The second interactive step, discectomy, has been assessed by Mirchi, et al [6] and the third interactive step, osteophyte removal by Reich, et al [18] have been previously reported.…”
Section: The Virtual Reality Simulator and The Simulated Scenariomentioning
confidence: 99%
See 3 more Smart Citations